Infectious illnesses in areas of violence and among refugees - V B Hans (International Journal of Tropical Medicines, 2026)
Infectious illnesses are a huge and ongoing hazard in conflict zones and among refugee populations. This is because frail health systems, population relocation, and poor living conditions all come together to make transmission risks higher. Armed conflict undermines vital public health infrastructure, such as vaccination programs, disease surveillance, water and sanitation systems, and access to medical care, resulting in the resurgence and proliferation of avoidable and treatable illnesses. Refugee camps are overcrowded, people are malnourished, they don’t have enough clean water, and they don’t have enough shelter, which makes them much more likely to get diseases including tuberculosis, measles, cholera, malaria, and acute respiratory infections. Also, impediments to getting healthcare, such feeling unsafe, not having legal status, and not having enough resources, make it take longer to get a diagnosis and treatment, which makes people sicker and more likely to die. Antimicrobial resistance is a developing concern in these environments due to disrupted treatment regimens and constrained diagnostic capabilities. This article looks at the epidemiology of infectious diseases in populations affected by conflict, the structural and social factors that lead to disease transmission, and the problems that humanitarian and public health solutions face. It also emphasises the need for coordinated action by countries around the world, better surveillance, more vaccinations, and including infectious disease control in humanitarian efforts. Dealing with infectious diseases in war-torn areas is not only a moral obligation, but it is also a key part of global health security.
Keywords: antimicrobial resistance; conflict zones; infectious diseases; public health infrastructure watching for diseases; refugee populations